Coronavirus disease 2019 mortality: a multivariate ecological analysis in relation to ethnicity, population density, obesity, deprivation and pollution. (August 2020) - Bray, I.; Gibson, A.; White, J.
Abstract: Background: There is emerging evidence about characteristics that may increase the risk of coronavirus disease 2019 (COVID-19) mortality, but they are highly correlated. Methods: An ecological analysis was used to estimate associations between these variables and age-standardised COVID-19 mortality rates at the local authority level. Results: Ethnicity, population density and overweight/obesity were all found to have strong independent associations with COVID-19 mortality, at the local authority level. Discussion: This analysis provides some preliminary evidence about which variables are independently associated with COVID-19 mortality and suggests that others (deprivation and pollution) are not directly linked. It highlights the importance of multivariate analyses to understand the factors that increase vulnerability to COVID-19. Highlights: A multivariate ecological analysis of Coronavirus disease 2019 (COVID-19) mortality by local authority was conducted. Non-white ethnicity was associated with increased COVID-19 mortality. Higher population density was associated with increased COVID-19 mortality. Overweight/obesity was associated with increased COVID-19 mortality. There was no evidence for an independent effect of pollution.